SUBJEK HUKUM INTERNASIONAL - Gede Bagus Prema Cahya Sani Putra (Jurnal Locus Delicti, 2022)
In individual municipal law, limited liability companies and public companies are recognized as each having a distinct legal personality, the provisions of which are limited by the relevant legislation. That law will determine the scope and nature of personality. Personality involves examining certain concepts in law such as status, capacity, competence, as well as the nature and extent of certain rights and obligations. “All states enjoy sovereign equality. They have the same rights and obligations and are equal members of the international community, regardless of economic, social, political or other differences.